2010
DOI: 10.1038/labinvest.2009.111
|View full text |Cite
|
Sign up to set email alerts
|

Rho/ROCK and MEK/ERK activation by transforming growth factor-α induces articular cartilage degradation

Abstract: Identification and characterization of therapeutic targets for joint conditions, such as osteoarthritis (OA), is exceedingly important for addressing the increasing burden of disease. Transforming growth factor-a (TGFa) is upregulated by articular chondrocytes in experimentally induced and human OA. To test the potential involvement of TGFa, which is an activator of epidermal growth factor receptor (EGFR) signaling, in joint degeneration and to identify signaling mechanisms mediating articular chondrocyte resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 50 publications
6
96
1
1
Order By: Relevance
“…Similar phenomenon has already been reported in IL-1-mediated MMP13 induction in articular chondrocyte, where MMP13 expression was blocked by the p38 inhibitor SB203580, but not by the MEK inhibitor PD98059 47 . In addition, we had shown that MEK inhibition reduced chondrocyte proliferation induced by TGF-alpha 48 . However, Chiu et al reported that CXCL12a did not activate p38 MAP kinase, and activated only ERK1/2 signaling that was responsible for the induction of MMP13 via activator protein 1 (AP-1) in human articular chondrocyte 23 .…”
Section: Discussionmentioning
confidence: 98%
“…Similar phenomenon has already been reported in IL-1-mediated MMP13 induction in articular chondrocyte, where MMP13 expression was blocked by the p38 inhibitor SB203580, but not by the MEK inhibitor PD98059 47 . In addition, we had shown that MEK inhibition reduced chondrocyte proliferation induced by TGF-alpha 48 . However, Chiu et al reported that CXCL12a did not activate p38 MAP kinase, and activated only ERK1/2 signaling that was responsible for the induction of MMP13 via activator protein 1 (AP-1) in human articular chondrocyte 23 .…”
Section: Discussionmentioning
confidence: 98%
“…Two groups examined the involvement of ROCK in reagent-induced phosphorylation of MEK, a downstream kinase of Cot/Tpl2. Treatment with transforming growth factor-␣ induced MEK activation through ROCK in rat chondrocytes (71). Cholinergic agonists induced activation of Rho and ROCK, which in turn activated MEK and ERK, in rat epithelial cells (72).…”
Section: Discussionmentioning
confidence: 99%
“…The most well-established role for Mig-6 in cancer cells is as a negative feedback regulator of EGFR (3)(4)(5)(6), and EGFR signaling is known to play an important role in bone development (28)(29)(30)(31). TGF-α, one of the ligands for EGFR, has been reported to be increased in human osteoarthritic joints (32), and it can induce articular cartilage degradation in animal models (33,34). EGFR signaling appears to be activated in the chondrocytes of the articular cartilage and in the osteophyte of the Mig-6 flox/flox ;Col2a1 Cre knee joints (Fig.…”
Section: Discussionmentioning
confidence: 99%